2006
DOI: 10.1111/j.2006.0908-8857.03655.x
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in blue tit Parus caeruleus plumage colour: within‐individual changes or colour‐biased survival?

Abstract: In many species of passerine birds yearlings display a less elaborate version of the adult secondary sexual traits, but the causes of such differences in ornamentation are not always well understood. We studied age‐related changes in blue tit Parus caeruleus UV/blue structural crown coloration, a sexually selected trait. In our Austrian study population, older blue tits, irrespective of sex, displayed on average a more ultraviolet (lower hue, higher UV chroma), more chromatic and brighter crown coloration than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 59 publications
5
67
0
Order By: Relevance
“…In these previous studies, survival was measured from one breeding season to the next, whereas for the present study, we measured survival of birds that were present in winter to the following breeding season, which could have caused a discrepancy. However, a recent study on an Austrian blue tit population also showed no evidence for crown color-related survival, while survival in this study was estimated from one breeding season to the next (Delhey and Kempenaers 2006). Possibly, plumage-based status signalling is more important in northerly blue tit populations, perhaps because these are less sedentary during winter.…”
Section: Uv Coloration and Over-winter Survivalmentioning
confidence: 66%
See 1 more Smart Citation
“…In these previous studies, survival was measured from one breeding season to the next, whereas for the present study, we measured survival of birds that were present in winter to the following breeding season, which could have caused a discrepancy. However, a recent study on an Austrian blue tit population also showed no evidence for crown color-related survival, while survival in this study was estimated from one breeding season to the next (Delhey and Kempenaers 2006). Possibly, plumage-based status signalling is more important in northerly blue tit populations, perhaps because these are less sedentary during winter.…”
Section: Uv Coloration and Over-winter Survivalmentioning
confidence: 66%
“…This enabled us to control our analyses for the potentially confounding effects of sitedependent dominance, i.e., the phenomenon that individuals are more dominant at sites closer to their own territory (Colquhoun 1942;De Laet 1984;Oberski and Wilson 1991;Dingemanse and De Goede 2004;Hansen and Slagsvold 2004). While controlling for sex, age, and distance to territory, we tested if (1) social dominance was related to crown UV reflectance and (2) individuals with higher UV reflectance had a greater probability of survival to the following breeding season as reported previously (Sheldon et al 1999;Griffith et al 2003; but see Delhey and Kempenaers 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Closer scrutiny of the predictability of such traits could not only be helpful for our understanding of behavioral predictability, they could also increase our mechanistic understanding of physiological traits themselves (Romero 2004). Another area of research where the study of predictability could prove fruitful is the study of animal signaling, where individuals could differ in the temporal variability of acoustic or variable morphological traits (Riebel and Slater 2003;Delhey and Kempenaers 2006). Finally, our results indicate that we should exercise caution when interpreting statistical analyses of behavioral data because nearly all parametric linear models assume that each individual has equal residual variance (but see Briffa et al 2013, where a unique residual variance is fitted to each individual and shown to provide a near-identical result to the simpler approach employed here).…”
Section: Discussionmentioning
confidence: 99%
“…Coloration often increases in individuals with age (Delhey & Kempenaers, 2006). Less colorful individuals have less chance to survive until adulthood (Pagani‐Nuñez & Senar, 2012).…”
Section: Resultsmentioning
confidence: 99%